Mars desert research station: Crew 138 - Roman Gonzalez, Avid (2015)
Crew 138 was comprised of a team of highly-skilled professionals with varied backgrounds who were selected by the Mars Society to undertake a two-week interdisciplinary expedition at the Mars Desert Research Station near Hanksville, Utah. The Crew's activities ranged in scope from preparing operational handbooks and checklists for the Mars Desert Research Station, performing hardware and logistical evaluations for future research at MDRS, an analysis of Google Earth as a tool for geological field mapping, evaluations of commercial-off-The-shelf engineering and electrical components, the design of a Mars EVA work day functional task battery, and assessing the viability for incorporating an exercise countermeasures hardware and program into the Mars Desert Research Station.